The sensitivity of photosynthesis to magnesium deficiency differs between rice (Oryza sativa L.) and cucumber (Cucumis sativus L.) - Meng, Xusheng; Bai, Song; Wang, Shiyu; Pan, Yonghui; Chen, Kehao; Xie, Kailiu; Wang, Min; Guo, Shiwei (Frontiers in Plant Science, 2023)
Magnesium is an essential macronutrient for plant photosynthesis, and in response to Mg deficiency, dicots appear more sensitive than monocots. Under Mg deficiency, we investigated the causes of differing photosynthetic sensitivities in a dicot and a monocot species. Rice (Oryza sativa L.) and cucumber (Cucumis sativus L.) were grown in hydroponic culture to explore their physiological responses to Mg deficiency stress. Both Mg-deficient rice and cucumber plants exhibited lower biomass, leaf area, Mg concentration, and chlorophyll content (Chl) compared with Mg-sufficient plants. However, a more marked decline in Chl and carotenoid content (Car) occurred in cucumber. A lower CO2 concentration in chloroplasts (Cc) was accompanied by a decrease in the maximum rate of electron transport (Jmax) and the maximum rate of ribulose 1,5-bisphosphate carboxylation (Vcmax), restricting CO2 utilization in Mg-deficient plants. Rice and cucumber photorespiration rate (Pr) increased under Mg deficiency. Additionally, for cucumber, Car and non-photochemical quenching (NPQ) were reduced under lower Mg supply. Meanwhile, cucumber Mg deficiency significantly increased the fraction of absorbed light energy dissipated by an additional quenching mechanism (Φf,D). Under Mg deficiency, suppressed photosynthesis was attributed to comprehensive restrictions of mesophyll conductance (gm), Jmax, and Vcmax. Cucumber was more sensitive to Mg deficiency than rice due to lower NPQ, higher rates of electron transport to alternative pathways, and subsequently, photooxidation damage.